2016
DOI: 10.1590/0100-69912016001008
|View full text |Cite
|
Sign up to set email alerts
|

The role of P16ink4a and P53 immunostaining in predicting recurrence of HG-CIN after conization treatment

Abstract: immunohistochemistry expression of p53 and p16 showed low sensitivity and low specificity as predictors of HG-CIN recurrence after conization treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 31 publications
(46 reference statements)
1
25
0
2
Order By: Relevance
“…The study by Cardoso et al 4 was one of the few that showed statistical significance between p16 ink4a overexpression and disease recurrence, as did Nam et al 25 . Fonseca et al 26 demonstrated that p16 ink4a was overexpressed in 43% of the recurrences, with high intensity in 58% of them, though this finding was not statistically significant. In a group of 90 patients with cervical intraepithelial neoplasia with overexpressed p16 ink4a and Ki67, there was progression in 15 cases (17%), two cases in the group of 25 patients with CIN I (8%) and 13 cases in the group of 65 patients with CIN II (20%) 22 .…”
Section: Discussionmentioning
confidence: 92%
“…The study by Cardoso et al 4 was one of the few that showed statistical significance between p16 ink4a overexpression and disease recurrence, as did Nam et al 25 . Fonseca et al 26 demonstrated that p16 ink4a was overexpressed in 43% of the recurrences, with high intensity in 58% of them, though this finding was not statistically significant. In a group of 90 patients with cervical intraepithelial neoplasia with overexpressed p16 ink4a and Ki67, there was progression in 15 cases (17%), two cases in the group of 25 patients with CIN I (8%) and 13 cases in the group of 65 patients with CIN II (20%) 22 .…”
Section: Discussionmentioning
confidence: 92%
“…In 43% of the recurrence group and 57% of the control group, p16 was present, with a sensitivity of 66%, a specificity of 49%, a positive predictive value of 42%, a negative predictive value of 72%, and accuracy of 56%. Thus, these results showed that p16 did not predict the recurrence of HSIL after treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…Fonseca et al [25] evaluated the predictive value of p16. They assessed 83 patients with HSIL, aged between 16 and 86 years, from 1999 to 2006.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…All skin samples were sent for routine pathological staining analyses. The paraffin-embedded and formalin-fixed skin were stained for immunohistochemistry using normal hematoxilin-eosin (H&E) staining; p53 expression with monoclonal mouse Anti-human P53 protein, clone DO-7 (as described in (Fonseca et al 2016)); p63 expression with mouse monoclonal, clone DAK-p63, core DNA-binding domain of human p63 protein reacting with TAp63 and ΔNp63 isoforms of p63); cKit/CD117 expression with rabbit polyclonal.…”
Section: Gene Expression Biomarkersmentioning
confidence: 99%